2015
DOI: 10.1116/1.4914316
|View full text |Cite
|
Sign up to set email alerts
|

Precursors for carbon doping of GaN in chemical vapor deposition

Abstract: Articles you may be interested in 3 ] have been investigated as precursors for intentional carbon doping of (0001) GaN in chemical vapor deposition. The carbon precursors were studied by comparing the efficiency of carbon incorporation in GaN together with their influence on morphology and structural quality of carbon doped GaN. The unsaturated hydrocarbons C 2 H 4 and C 2 H 2 were found to be more suitable for carbon doping than the saturated ones, with higher carbon incorporation efficiency and a reduced eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 34 publications
2
38
0
1
Order By: Relevance
“…In a recent study, 9 we identified several potential carbon containing gases that could be used for in-situ carbon doping of GaN.…”
Section: à3mentioning
confidence: 99%
“…In a recent study, 9 we identified several potential carbon containing gases that could be used for in-situ carbon doping of GaN.…”
Section: à3mentioning
confidence: 99%
“…Most interesting is the evaluation of the effect of growth rate on carbon concentration. In work [5] (and likely in [6,7]), the growth rate of GaN:C epilayers was only 0.65 μm/h. This value is too low for production.…”
Section: Introductionmentioning
confidence: 98%
“…These works are a significant step in the development of controllable carbon doping of gallium nitride. However, in the recent works [6][7][8], the authors have focused on properties of device structures while the main objective of paper [5] was a comparison of carbon incorporation efficiency for a number of carbon precursors and growth temperature was the only parameter studied. An observed tendency -increase of carbon concentration with temperature reduction -was the same as for background carbon doping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon impurities are always present as a contaminant in MOCVD grown GaN, but modifying the growth conditions or adding an external source can increase the concentration above 10 19 cm -3 [5]. The carbon can be substituted on either the Ga or N site and can form a variety of complexes, with each species having different trap characteristics.…”
Section: A the "Ideal" C-doped Hemtmentioning
confidence: 99%